2020
DOI: 10.1101/2020.10.18.344275
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cooperation-based sperm clusters mediate sperm oviduct entry and fertilization

Abstract: Sperm cooperation has been observed in multiple species, yet its existence and benefit for reproductive success in mammals remains underexplored. Here, combining tissue-clearing with deep three-dimensional imaging, we demonstrate that postcopulatory mouse sperm congregate into unidirectional sperm cooperative clusters at the utero-tubal junction (UTJ), a key physical barrier for passage into the oviduct. Reducing sperm number in male mice by unilateral vasoligation or busulfan-treatment impairs sperm cluster f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In invertebrates, the swimming velocity of fishfly sperm increases with number of sperm in a bundle (Hayashi 1998), but in a marine snail, there is no differences in swimming speed between paired and single sperm (Ishijima et al 1999). Although it was beyond the scope of this study, additional work is needed to elucidate the conditions within the female reproductive tract (e.g., fluid viscosity) so that they can be approximated in vitro , or observed in vivo (Ishikawa et al 2016; Wang and Larina 2018; Qu et al 2020), to determine if sperm aggregation does indeed allow for more efficient migration through viscous female secretions (Moore and Taggart 1995; Suarez 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In invertebrates, the swimming velocity of fishfly sperm increases with number of sperm in a bundle (Hayashi 1998), but in a marine snail, there is no differences in swimming speed between paired and single sperm (Ishijima et al 1999). Although it was beyond the scope of this study, additional work is needed to elucidate the conditions within the female reproductive tract (e.g., fluid viscosity) so that they can be approximated in vitro , or observed in vivo (Ishikawa et al 2016; Wang and Larina 2018; Qu et al 2020), to determine if sperm aggregation does indeed allow for more efficient migration through viscous female secretions (Moore and Taggart 1995; Suarez 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, while investigating the functions of sperm-specific proteins in gene knockout (KO) mouse strains, it was found that a certain strain of KO sperm with normal morphology and motility were unable to pass through the UTJ [ 117 ]. Subsequently, the deletion of genes for a number of sperm-specific proteins resulted in the same infertile male phenotype [ 118 ]. The proteins produced by these genes were either plasma membrane proteins or were involved in bringing proteins to the plasma membrane.…”
Section: Apparent Co-evolution Of Sperm and Female Reproductive Tract Physical Traitsmentioning
confidence: 99%
“…This seemed to indicate that sperm passage through the UTJ might involve some sort of molecular interaction between one or more sperm proteins and receptors lining the oviduct. However, recently, evidence has arisen to indicate that the proteins play a role in aggregating sperm in the uterus, and it has been proposed that the aggregated sperm, which are aligned in the same direction, are able to push their way into the UTJ, or push open the UTJ, which is something that single sperm seem unable to do [ 118 ]. This interesting discovery requires further investigation as a previously unknown function of sperm aggregation.…”
Section: Apparent Co-evolution Of Sperm and Female Reproductive Tract Physical Traitsmentioning
confidence: 99%